ASSESSMENT OF SONDONG FISHERIES AT DUMAI CITY FISH LANDING BASE - Winda Safitri; Eko Sri Wiyono; Sugeng Hari Wisudo (Department of Fisheries Resources Utilization, Faculty of Fisheries and Marine Science, IPB University, Bogor, Indonesia, 2026)
Fishing activities in the PPI of Dumai City are dominated by the use of sondong (push net) fishing gear, a type of shrimp fishing gear classified as a type of push net. Based on PERMEN KP No. 36 of 2023, the permitted method of operating push nets is operation without using a boat. However, one region in Indonesia still uses sondong with the help of boats as occurs in the PPI of Dumai City. This study aims to describe the sondong fishery in the PPI of Dumai City, Riau Province. This study was conducted from October to November 2025, data was collected through interviews, surveys, and direct observation. Primary data was obtained directly from fishermen, PPI staff, and Dumai City DKP staff, while secondary data was obtained from fishing logbooks and port statistics. The results of the study indicate that the main catch of the sondong fishing gear is white shrimp (Penaeus sp). The fishing fleet used is a boat with a length of 12 meters, a width of 2.5 meters, and a height of 1.2 meters. It is driven by a 24 HP Dongfeng engine and operated by 1-2 crew members. The sondong fishing area covers the waters of Sintahulu, Tianjung, Teluk Dalam, and Senepis. The sondong nets used are made of dark green multifilament polyethylene and consist of four sections. Key words: Dumai city PPI, penaeid shrimp, sondong fishing gear